Genome-wide scan in Portuguese Island families implicates multiple loci in bipolar disorder: Fine mapping adds support on chromosomes 6 and 11 - Pato, Carlos N. (2004)
As part of an extensive study in the Portuguese Island population of families with multiple patients suffering from bipolar disorder and schizophrenia, we performed an initial genome-wide scan of 16 extended families with bipolar disorder that identified three regions on chromosomes 2, 11, and 19 with genome-wide suggestive linkage and several other regions, including chromosome 6q, also approached suggestive levels of significance. Dick et al. [2003: Am J Hum Genet 73:107-114] recently reported in a study of 250 families with bipolar disorder a maxLOD score of 3.61 near marker D6S1021 on chromosome 6q. This study replicates this finding having detected a peak NPL = 2.02 (P = 0.025) with the same marker D6S1021(104.7 Mb). Higher-density mapping provided additional support for loci on chromosome 6 including marker D6S1021 with an NPL = 2.59 (P = 0.0068) and peaking at marker D6S1639 (125 Mb) with an NPL = 3.06 (P = 0.0019). A similar pattern was detected with higher-density mapping of chromosome 11 with an NPL = 3.15 (P = 0.0014) at marker D11S1883 (63.1 Mb). Simulations at the density of our fine mapping data indicate that less than 1 scan out of 10 would find two such scores genome-wide in the same scan by chance. Our findings provide additional support for a susceptibility locus for bipolar disorder on 6q, as well as, suggesting the importance of denser scans. Published 2004 Wiley-Liss, Inc.